Sudden Unexpected Death and the Mammalian Dive Response: Catastrophic Failure of a Complex Tightly Coupled System - Vincenzi, Frank F. (Frontiers in Physiology, 2019)
Charles Perrow introduced the concept that catastrophic failures of complex high-risk technical systems, such as nuclear power plants, are ‘normal’ or ‘system’ accidents that take the lives of hundreds of people or shorten or cripple the lives of many others. In tightly coupled complex systems, when two or more factors or events interact in unanticipated ways, catastrophic failures of high-risk technical systems happen rarely, but quickly. Safety devices are commonly built into complex systems to avoid disasters but are often part of the problem. The hypothesis advanced herein is that the human body may also be considered as a complex tightly coupled system at risk of rare catastrophic failure (sudden unexpected death) when certain factors or events interact. The mammalian dive response is a built-in safety feature of the body that normally conserves oxygen during apnea. However, upon the interaction of certain factors or events, the mammalian dive response facilitates potentially fatal heart rhythms and, rarely, sudden cardiac death. In some, cases of sudden infant death syndrome (SIDS), sudden unexpected death in epilepsy (SUDEP), and sudden cardiac death in water (SCDIW, fatal drowning), activation of the mammalian dive response is the final mechanistic pathway to sudden death. There is no single cause in any of these scenarios, but rather a wide and variable array of, unanticipated, often unknown, factors or events that interact to activate the mammalian dive reflex. In any particular case, the relevant risk factors or events might include some combination of genetic (e.g., long QT syndrome), developmental (e.g., neuropathologic), metabolic, (e.g., hypokalemia), disease (e.g., epilepsy), environmental (e.g., cold shock or overheating) or operational (e.g, prone sleeping or consumption of alcohol), or other influences. The interacting factors or events that are the underlying causes differ from case to case. Identification of important risk factors may help reduce the incidence of sudden unexpected death, but determination of a single cause in any of these scenarios is unlikely. The common thread among these seemingly different scenarios is the activation of a safety feature of the human body that contributes to the mechanism of death.